Mycophenolic acid inhibits SLE-associated cytokine expression and promotes apoptosis of peripheral blood mononuclear cells from patients with systemic lupus erythematosus - Su Ding-lei; Wang Hui-juan; Ji Xiao-hui; Li Yuan-yuan; Xuan Heng-bao; Heng Chun; Li Yu-feng (Acta Pharmacologica Sinica; Vol 27, No 8 (August 2006): Acta Pharmacologica Sinica, 2016)
Aim: To investigate the effect of the novel immunosuppressant mycophenolic acid (MPA) on cytokine production and apoptosis of the peripheral blood mono-nuclear cells (PBMC) of patients with systemic lupus erythematosus (SLE). Methods: The levels of IL-10, IL-12, IFN-, sFas and sFasL in the supernatants of cultured PBMC from 41 SLE patients was determined by the ABC-ELISA method. The percentage of IFN-γ+IL-10-, IFN-γ-IL-10+, and IFN-γ+IL-10+ subsets in CD4+ cells were detected by three-color flow cytometry. The percentage of apoptotic Th cells was detected by AV-FITC/PI flow cytometry. Samples from 22 sex- and age-comparable healthy people were used as normal controls. Results: The levels of IL-10, IL-12, and IFN-γ were all significantly elevated in the supernatants of cultured PBMC from SLE samples, compared with normal controls. The enhanced productions of IL-10, IL-12, and IFN-γ by PBMC from SLE both spontaneously and stimulated by phytohaemagglutinin (PHA) were significantly reduced by MPA. The percentages of CD4+IFN-γ-IL-10+ and CD4+IFN-γ+IL-10+ cell subsets in cultured PBMC from SLE were significantly increased, but decreased when MPA was added into the culture. After being cultured in vitro for 48 h, the PBMC of SLE patients showed a higher secretion of sFasL as well as a higher percentage of apoptosis. MPA significantly increased the apoptotic percentage of SLE PBMC, but reduced the secretion of sFasL and sFas. Conclusion: MPA reduces the abnormal production of SLE-associated cytokines, such as IL-10, IL-12, and IFN-γ; inhibits the increase of CD4+IFN-γ+IL-10, CD4+IFN-γ-IL-10+ and CD4+IFN-γ+IL-10+ subset; and promotes the apoptosis of PBMC in SLE patients, which may be associated with the therapeutic mechanism of MPA for SLE.